Correlations of echocardiographical parameters in women, which underwent laparoscopic cholecystectomy - Strilchuk, Larissa; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Strilchuk Larissa, Zukow Walery. Correlations of echocardiographical parameters in women, which underwent laparoscopic cholecystectomy. Journal of Education, Health and Sport. 2015;5(4):251-258. ISSN 2391-8306. DOI: 10.5281/zenodo.16924 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A251-258 https://pbn.nauka.gov.pl/works/554866 http://dx.doi.org/10.5281/zenodo.16924 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. UDK: 616.366-089.616-074+616-072.7 Correlations of echocardiographical parameters in women, which underwent laparoscopic cholecystectomy Larissa Strilchuk1, Walery Zukow2 1Danylo Halytsky Lviv National Medical University, Lviv, Ukraine 2Kazimierz Wielki University, Bydgoszcz, Poland Abstract. Laparoscopic cholecystectomy (LCE) holds the 1st place among abdominal surgeries. Pathology of the biliary system is associated with female sex, because estrogens increase bile lithogenicity. One of the peculiarities of biliary system diseases in women is combination of them with cardiovascular diseases. Specific patterns of heart changes in women, which underwent LCE, are not clearly established yet. That’s why we held a retrospective analysis of 100 case histories of women, which underwent LCE. Among analysed women frequency of arterial hypertension was 79%; obesity was diagnosed in 52%, overweight – in 30% of patients. Median of index of left ventricle (LV) myocardium weight in examined women exceeded normal values (108.34 g/m2 with the limit to 95 g/m2). Median of relative thickness ofLV wall indicated presence of eccentric hypertrophy. In examined patients we also revealed signs of hypertrophic type of diastolic dysfunction: decrease of speed E on the background of increase of speed A and decrease of E/A ratio to 0.7. Erythrocyte sedimentation rate (ESR) in our patients directly correlated with left atrium size, thicknesses ofLV posterior wall and interventricular septum, end-systolic volume,LV myocardium weight and its indexed value. ESR also reversely correlated with ejection fraction (all r<0,05). Echocardiographical parameters also correlated with body weight, height, body mass index, age, systolic and diastolic blood pressure. Key words: cholelithiasis, laparoscopic cholecystectomy, hypertension, heart, left ventricle.